Cultivar Variation in Hormonal Balance Is a Significant Determinant of Disease Susceptibility to Xanthomonas campestris pv. campestris in Brassica napus - Islam, Md. Tabibul; Lee, Bok-Rye; Park, Sang-Hyun; La, Van Hien; Bae, Dong-Won; Kim, Tae-Hwan (Frontiers in Plant Science, 2017)
This study aimed to directly elucidate cultivar variation in disease susceptibility and disease responses in relation to hormonal status in the interaction of Brassica napus cultivars and Xanthomonas campetris pv. campestris (Xcc), the causal agent of black rot disease. Fully expanded leaves of six B. napus cultivars (cvs. Capitol, Youngsan, Saturnin, Colosse, Tamra, and Mosa) were inoculated with Xcc. At 14 d post-inoculation (dpi) with Xcc, cultivar variation in susceptibility or resistance was interpreted with defense responses as estimated by redox status, defensive metabolites, and expression of phenylpropanoid synthesis-related genes in relation to endogenous hormonal status. Disease susceptibility of six cultivars was distinguished by necrotic lesions in the Xcc-inoculated leaves and characterized concurrently based on the higher increase in reactive oxygen species (ROS) and lipid peroxidation. Among these cultivars, as the susceptibility was higher, the ratios of abscisic acid (ABA)/jasmonic acid (JA) and salicylic acid (SA)/JA tended to increase with enhanced expression of SA signaling regulatory gene NPR1 and transcriptional factor TGA1and antagonistic suppression of JA-regulated gene PDF 1.2. In the resistant cultivar (cv. Capitol), accumulation of defensive metabolites with enhanced expression of genes involved in flavonoids (CHS), proanthocyanidins (ANR), and hydroxycinnamic acids (F5H) biosynthesis and higher redox status were observed, whereas the opposite results were obtained for susceptible cultivars (cvs. Mosa and Tamra). These results clearly indicate that cultivar variation in susceptibility to infection by Xcc was determined by enhanced alteration of the SA/JA ratio, as a negative regulator of redox status and phenylpropanoid synthesis in the Brasica napus-Xcc pathosystem.